(untitled) - Packer, James Innell; (1926-2020) (U.S.A, 2008)
We face decisions every day--some big, some small. As Christians, we seek to submit the choices we make to God's will. Unfortunately, for many the process of discerning God's will has become fraught with fear and confusion, leading to such questions as Does God guide? If so, how? How will I know when he does? What if I make a mistake? J.I. Packer and Carolyn Nystrom seek to free us from such fear. Beginning with an exploration of Psalm 23, they show that in his covenant role as our Good Shepherd, God has promised to both guides and guard us, his sheep. We need not doubt that he will lovingly grant the guidance we need as we seek him. And we can take comfort that just as a shepherd retrieves and redirects sheep that go off course, he will do the same for us. In this rich study of divine guidance, Packer and Nystrom show the importance of cultivating a lifestyle of Bible-based wisdom and discernment. And they take seriously the role of the Holy Spirit in guiding his people, neither downplaying the supernatural element of divine guidance nor elevating it beyond our reach to the level of the `super-spiritual,` or worse, the superstitious.
Keywords: Providence and government of God -- Christianity